Experimental Learning Strategies in Improving the Quality of Learning in Islamic Religious Education - Muhammad Ashari; Besse Marjani Alwi; Usman (PT Bukuloka Literasi Bangsa, 2026)
ABSTRACT This study aims to analyze the implementation of experimental learning strategies in improving the quality of Islamic Religious Education learning at UPTD SDN 267 Pincengpute. Experimental learning strategies are learning methods that emphasize students' direct experiences through experiments and observation activities to build in-depth understanding of concepts. This study uses a qualitative descriptive method of analysis with data collection techniques through observation, interviews, and documentation. The subjects of the study were teachers and students of grade V at UPTD SDN 267 Pincengpute. The results of the study show that the implementation of experimental learning strategies in PAI learning can increase students' activities, motivation, and understanding of learning materials. The stages of implementing experimental learning include planning, experiment implementation, observation, data analysis, and conclusion. The advantages of this strategy include improving students' critical thinking skills, creativity, and scientific skills. However, there are several limitations such as requiring longer time, adequate laboratory facilities, and teachers' readiness to design experiments that are in accordance with PAI materials. This study recommends the importance of improving teachers' competence in designing contextual experimental learning and improving learning support infrastructure. Keywords: Experimental Learning Strategies, Islamic Religious Education, Learning Quality